Relations between school bullying, friendship processes, and school context. Issue 2 (3rd April 2022) - Strindberg, Joakim; Horton, Paul
ABSTRACT: Background: Despite considerable anti–bullying efforts and greater awareness of the social processes underpinning bullying, bullying is still a serious problem across schools in many countries. In exploring the social processes that contribute to school bullying, research indicates complex relationships between bullying and the maintenance and building of friendships. While such findings provide important information about the social context of school bullying, more needs to be understood about the institutional context within which school bullying – and friendship – occur. Purpose: The aim of this study is to better understand how school bullying relates to friendship processes, and how these are, in turn, influenced by the institutional constraints of the school context. Method: The findings discussed draw on 3 months of ethnographic fieldwork conducted at one Swedish elementary school. The fieldwork involved participant observations, as well as semi–structured group interviews with 34 sixth-grade pupils (approx. 12 years of age), which were conducted towards the end of the fieldwork. Data were analysed thematically. Findings: The analysis highlighted the importance of friendships to pupils but also identified the ways in which understandings of friendship relations were closely tied to the importance of social perceptions and the organisational constraints of the school context. Conclusions: Taken together, the findings suggest that school bullying cannot be de–contextualised from the social and institutional contexts of school but may rather be connected to the perceived need for control in that particular arena. The study draws attention to how the complex relations between bullying, friendship and school context need to be better understood, in order to support efforts to prevent school bullying.